Biomaterial-based endochondral bone regeneration: A shift from traditional tissue engineering paradigms to developmentally inspired strategies - Kelly, Daniel; Sheehy, Eamon J.; O'Brien, Fergal J. (My University, 2019)
There is an urgent, clinical need for an alternative to the use of autologous grafts for the ever increasing number of bone grafting procedures performed annually. Herein, we describe a developmentally inspired approach to bone tissue engineering, which focuses on leveraging biomaterials as platforms for recapitulating the process of endochondral ossification. To begin, we describe the traditional biomaterial-based approaches to tissue engineering that have been investigated as methods to promote in vivo bone regeneration, including the use of three-dimensional biomimetic scaffolds, the delivery of growth factors and recombinant proteins, and the in vitro engineering of mineralized bone-like tissue. Thereafter, we suggest that some of the hurdles encountered by these traditional tissue engineering approaches may be circumvented by modulating the endochondral route to bone repair and, to that end, we assess various biomaterials that can be used in combination with cells and signaling factors to engineer hypertrophic cartilaginous grafts capable of promoting endochondral bone formation. Finally, we examine the emerging trends in biomaterial-based approaches to endochondral bone regeneration, such as the engineering of anatomically shaped templates for bone and osteochondral tissue engineering, the fabrication of mechanically reinforced constructs using emerging three-dimensional bioprinting techniques, and the generation of gene-activated scaffolds, which may accelerate the field towards its ultimate goal of clinically successful bone organ regeneration.
PUBLISHED
Keywords: Alternative to the use of autologous grafts; Scaffold; Mesenchymal stem cell; Endochondral ossification; Hypertrophy; Biochemical factors; Oxygen tension; alternative to the use of autologous grafts